The Development of Ontology in Hadith Studies: A Bibliometric Analysis - Ikmal Hafiz Jamal; Siti Fatimah Mohd Tawil; Norzulaili Mohd Ghazali; Amna Javed (Penerbit Universiti Kebangsaan Malaysia (UKM Press), 2026)
Indexed by WOS/ MyCite